Karbon Tersimpan Pada Kawasan Sistem Agroforestry Di Register 39 Datar Setuju Kphl Batutegi Kabupaten Tanggamus - Dian Aprianto; Christine Wulandari; Niskan Walid Masruri (Jurnal Sylva Lestari, 2016)
Datar Setuju Resort is the one of six resort located in Register 39 KPHL Batutegi. This area is managed by implementing agroforestry system. Research aims to determine amount of stock carbon applied by publics in Register 39 Datar Setuju, held on March 2015 at Register 39 Datar Setuju KPHL Batutegi Tanggamus Regency. Beside to knowing amount of the stock carbon, this research also conducted to determine the dominant vegetation. Reseachers used Summed Dominance Ratio (SDR) and Importance Value Index (IVI) methods to determine the most dominant vegetations and used allometric equation to find out amount biomass and necromass of trees. Research results show that the most dominant vegetation on tree phase was cemara (Casuarina junghuniana) IVI large was 109,91%, for pale phase was dadap (Erythrina sp.) IVI large was 300%, for stake phase was kopi (Coffea arabica) IVI large was 300%, and for seedling phase was rumput teki (Cyperus rotundus) IVI large was 200%. Stock carbons at agroforestry system area Register 39 Datar Setuju KPHL Batutegi on HKm Sinar Harapan amount of 123,33 ton/ha, on HKm Bina Wana Jaya 1 amount of 265,20 ton/ha, and of HKm Bina Wana Jaya 2 amount of 146,20 ton/ha, average of stock carbon value at Register 39 Datar Setuju amount of 178,24 ton/ha. Keywords: stock carbon, agroforestry